BAGS-Shiny - Andersson, Anders (SciLifeLab Serve, 2026)
Biome-specific gene catalogues have been recovered for many environments using shotgun metagenomics, followed by assembly and gene calling on the assembled contigs. We recently proposed a novel mix-assembly strategy, combining individual and co-assembly approaches, and used this approach to assemble an extensive non-redundant gene set from 124 Baltic Sea metagenome samples. The Baltic Sea Gene Set (BAGS v1.1) comprises 66.53 million functionally and taxonomically annotated genes. To enable interactive exploration of this gene catalogue we have developed an RShiny application, BAGS-Shiny, that allows users to perform searches by sequence similarity (BLAST) and/or taxonomic and functional annotation. The gene catalogue and web application will serve as valuable tools for exploring microbial gene functions in brackish ecosystems.